2023
DOI: 10.1093/bjs/znad018
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in the standard of care for infrarenal abdominal aortic aneurysm repair, and risk of major adverse cardiovascular events and death

Abstract: Background This study investigated whether sex-specific differences in preoperative/perioperative standard of care (SOC) account for disparity in outcomes after elective infrarenal abdominal aortic aneurysm repair. Methods This was a retrospective cohort study of elective infrarenal abdominal aortic aneurysm repairs (2013–2020) using depersonalized patient-level National Vascular Registry data. SOC was defined for waiting tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…3,4 Previous meta-analysis investigating gender differences in vascular surgery reported that women had an equal if not higher prevalence of peripheral arterial disease (PAD), more severe disease at presentation and often have poorer outcomes. 5 Do the present data dispel or propagate the gender gap in healthcare? At first glance, these data could be regarded as cause for optimism and an absence of any differential outcomes in these Swedish vascular patients.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…3,4 Previous meta-analysis investigating gender differences in vascular surgery reported that women had an equal if not higher prevalence of peripheral arterial disease (PAD), more severe disease at presentation and often have poorer outcomes. 5 Do the present data dispel or propagate the gender gap in healthcare? At first glance, these data could be regarded as cause for optimism and an absence of any differential outcomes in these Swedish vascular patients.…”
mentioning
confidence: 90%
“…Within cardiovascular surgery, women have been shown regularly to have poorer outcomes; notably after coronary artery surgery and aortic aneurysm repair 3,4 . Previous meta‐analysis investigating gender differences in vascular surgery reported that women had an equal if not higher prevalence of peripheral arterial disease (PAD), more severe disease at presentation and often have poorer outcomes 5 …”
mentioning
confidence: 99%